-4^4= -4*-4*-4*-4
-4*-4=16
16*-4=-64
-64*-4= 256
Final answer: 256
is the standard form of the given expression
The given expression is:
![=-3(x+3)^{2} -3+3x\\\\=-3*(x^{2} +2*3*x+3^{2} )-3+3x\\\\=-3x^{2} -3*6x-3*9-3+3x\\\\=-3x^{2} -18x-27-3+3x\\\\=-3x^{2} -15x-30\\\\=-3(x^{2} +5x+10)](https://tex.z-dn.net/?f=%3D-3%28x%2B3%29%5E%7B2%7D%20-3%2B3x%5C%5C%5C%5C%3D-3%2A%28x%5E%7B2%7D%20%2B2%2A3%2Ax%2B3%5E%7B2%7D%20%29-3%2B3x%5C%5C%5C%5C%3D-3x%5E%7B2%7D%20-3%2A6x-3%2A9-3%2B3x%5C%5C%5C%5C%3D-3x%5E%7B2%7D%20-18x-27-3%2B3x%5C%5C%5C%5C%3D-3x%5E%7B2%7D%20-15x-30%5C%5C%5C%5C%3D-3%28x%5E%7B2%7D%20%2B5x%2B10%29)
This is the standard form of the given expression.
Learn more about Simplifying expression here brainly.com/question/723406
#SPJ4
We can solve this problem by using the distance formula. The distance formula is:
We can now put in values and solve.
![\sqrt{16 + 144}](https://tex.z-dn.net/?f=%20%5Csqrt%7B16%20%2B%20144%7D%20)
Answer:
y = 6x - 2
Step-by-step explanation:
slope intercept form is y = mx + b
m = slope
b = y-intercept
They give us the slope (m) which is 6 and the y-intercept (b) which is -2. PLug it into the equation
y = mx + b
y = 6x - 2